AN INVESTIGATION ON TIME MANAGEMENT AND COMMUNICATION SKILLS OF PHYSICAL EDUCATION AND SPORT STUDENTS - Umit Dogan USTUN; Adnan ERSOY; Arzu BERK (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
This study aimed to investigate physical education and sport students' time management understandings, communication skills and the relationship between. A total of 233 randomly chosen students voluntarily participated for the study. In the study as data gathering tools in addition to personal information form Time Management and Communication Skills Scales were used. In the evaluation of data, first normality of the data assessed and then Independent Samples t Test, One Way ANOVA and Pearson Correlation statistical methods were used as hypotheses tests. As a result this study showed a) females have better mental and behavioural communication skills than males b) department of education has no effect on communication skills c) males have a better time management understanding than females d) recreation students have a better time management understanding than other department students and e) if time wasters decreases behavioural communication skill improves.